Implementation Of The Multi-Attribute Utility Theory (Maut) Algorithm In The Web-Based Performance Evaluation System For The Administrators Of Nurul Hayah Islamic Boarding School - Fitria, Alfina; Nada, Noora Qotrun; Dewanto, Febrian Murti (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Islamic Boarding School as an educational institution that focuses on character, moral, and religious formation that has an organizational structure involving many administrators with their respective roles and responsibilities. With this, an Islamic boarding school must improve the quality of management of the administrators by evaluating the performance of the administrators. In this study, we tried to select the best administrators at the Nurul Hayah Islamic Boarding School using the Multi-Attribute Utility Theory (MAUT) method. I used five main assessment criteria: discipline, loyalty, accountability, leadership, and educational background. To build the system, I applied the Extreme Programming (XP) methodology with the PHP programming language, MySQL database, and Visual Studio Code development environment. The sample was obtained from the data of the administrators of the education section of the Nurul Hayah Islamic Boarding School. With the weights that have been determined for each criterion, this study successfully identified Dimas as the administrator with the best performance, and obtained a score of 14.6667 as the best administrator at the Nurul Hayah Islamic Boarding School. With this, it is stated that the study using the MAUT method to determine the best administrator was successful.